2023
DOI: 10.2106/jbjs.oa.22.00106
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Admission Immunocoagulopathy as an Indicator for In-Hospital Mortality in Patients with Necrotizing Fasciitis

Abstract: Background:Necrotizing fasciitis is a rapidly progressive infection with a high mortality rate. Pathogens evade the host containment and bactericidal mechanisms by hijacking the coagulation and inflammation signaling pathways, leading to their rapid dissemination, thrombosis, organ dysfunction, and death. This study examines the hypothesis that measures of immunocoagulopathy upon admission could aid in the identification of patients with necrotizing fasciitis at high risk for in-hospital mortality.Methods:Demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…NLR/PLR in relation to adverse outcomes (morbidity and mortality) has been studied repeatedly in a variety of settings, including cancer, chronic/acute medical conditions or trauma. 7 , 10 , 11 , 16 , 17 However, specifying at NF, there were only two studies evaluating the utility of NLR/PLR: Ravindhran et al 18 suggested that a preoperative NLR of >7.5, but not PLR, significantly increased the risk of morbidity/mortality, and Johnson et al 26 found a moderate correlation of NLR with in-hospital mortality, which could be further improved by evaluating the ratio of NLR to platelet count. Our findings showed that both NLR and PLR were independently associated with mortality in patients with NF, confirming this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…NLR/PLR in relation to adverse outcomes (morbidity and mortality) has been studied repeatedly in a variety of settings, including cancer, chronic/acute medical conditions or trauma. 7 , 10 , 11 , 16 , 17 However, specifying at NF, there were only two studies evaluating the utility of NLR/PLR: Ravindhran et al 18 suggested that a preoperative NLR of >7.5, but not PLR, significantly increased the risk of morbidity/mortality, and Johnson et al 26 found a moderate correlation of NLR with in-hospital mortality, which could be further improved by evaluating the ratio of NLR to platelet count. Our findings showed that both NLR and PLR were independently associated with mortality in patients with NF, confirming this relationship.…”
Section: Discussionmentioning
confidence: 99%